2021
DOI: 10.3389/fpls.2021.700273
|View full text |Cite
|
Sign up to set email alerts
|

Bioformulation of Silk-Based Coating to Preserve and Deliver Rhizobium tropici to Phaseolus vulgaris Under Saline Environments

Abstract: Seed priming has been for a long time an efficient application method of biofertilizers and biocontrol agents. Due to the quick degradation of the priming agents, this technique has been limited to specific immediate uses. With the increase of awareness of the importance of sustainable use of biofertilizers, seed coating has presented a competitive advantage regarding its ability to adhere easily to the seed, preserve the inoculant, and decompose in the soil. This study compared primed Phaseolus vulgaris seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…More recently, the use of silk fibroin-a structural protein extracted from Bombyx mori cocoons in the design of functional seed coatings has opened up new possibilities for sustainable agriculture on marginal lands. [43,82,83] A recent example showcases the use of silk fibroin in combination with trehalose as seed coatings that encapsulate, preserve, and deliver Rhizobium tropici to Phaseolus vulgaris seeds upon sowing, [82] which effectively boosted germination and seedling growth in saline soils (Figure 2a-d). Such biomaterial formulation for seed coatings synergistically employs the film-forming, payload encapsulation, preservation, and tunable biodegradation capabilities of silk fibroin and the ability of trehalose to support survival of rhizobacteria during desiccation and resuscitation.…”
Section: Seed Coatingmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, the use of silk fibroin-a structural protein extracted from Bombyx mori cocoons in the design of functional seed coatings has opened up new possibilities for sustainable agriculture on marginal lands. [43,82,83] A recent example showcases the use of silk fibroin in combination with trehalose as seed coatings that encapsulate, preserve, and deliver Rhizobium tropici to Phaseolus vulgaris seeds upon sowing, [82] which effectively boosted germination and seedling growth in saline soils (Figure 2a-d). Such biomaterial formulation for seed coatings synergistically employs the film-forming, payload encapsulation, preservation, and tunable biodegradation capabilities of silk fibroin and the ability of trehalose to support survival of rhizobacteria during desiccation and resuscitation.…”
Section: Seed Coatingmentioning
confidence: 99%
“…A follow‐up study compared the performance of Phaseolus vulgaris seeds coated by a thin film of silk fibroin, trehalose, and Rhizobium tropici to seeds primed with Rhizobium tropici and trehalose, respectively. [ 43 ] The results showed that coated seeds exhibited the highest germination rate in soils of increasing salinity and more articulated roots were developed from coated seeds compared to primed seeds and untreated controls.…”
Section: Sustainable Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…Seed priming resulted in synchronized emergence, and uniform stand establishment due to a decline in the lag time to imbibition and a better repair of metabolic segments and osmotic adjustment [ 8 , 9 ]. Nevertheless, seed priming is facing many challenges, such as product conservation, viability losses during storage, and difficulties in upscaling management [ 2 , 10 ]. Moreover, this makes the process time-consuming and cumbersome when priming large quantities of seeds that require subsequent drying.…”
Section: Introductionmentioning
confidence: 99%